Sample preparation method and determination method of tantalum-aluminum alloy for hydrogen content detection
Through the sample preparation method of ultrasonic pickling, water washing and organic solvent washing on tantalum aluminum alloy samples, the problem of impurity interference in the detection of hydrogen content of tantalum aluminum alloy is solved, and the determination accuracy is significantly improved.
Patent Information
- Application Number
- CN202411830323.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
AI Technical Summary
When detecting the hydrogen content in tantalum aluminum alloy, the prior art is affected by the alloy surface impurities and oxides, resulting in low measurement accuracy and lack of appropriate pretreatment methods.
A sample preparation method is used to pretreat the tantalum aluminum alloy sample, including placing the sample in a mixed acid solution for ultrasonic pickling, followed by water washing and organic solvent washing to obtain a tantalum aluminum alloy sample for detection.
By optimizing the pickling pretreatment process, it can effectively remove impurities and oxides on the surface of tantalum aluminum alloy, avoid corrosion and loss of aluminum components, reduce reagents and impurities residues, and improve the accuracy of hydrogen content measurement.
Smart Images

Figure BDA0005185393850000091 
Figure BDA0005185393850000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of element analysis, and relates to a sample preparation method for hydrogen content detection, and in particular to a sample preparation method and a determination method of a tantalum-aluminum alloy for hydrogen content detection. Background Art
[0002] Tantalum aluminum alloys are widely used in the aerospace field. Tantalum aluminum alloys have extremely strong oxidation resistance in high-temperature environments, which can effectively prevent the formation of oxides on the metal surface and reduce the peeling of the coating or material surface. This performance is particularly important for high-temperature areas such as the combustion chamber and turbine blades of aircraft engines. Because long-term operation of these components will lead to the accumulation of oxide layers and reduced structural strength, based on the excellent oxidation resistance and high-temperature stability of tantalum aluminum alloys, the use of tantalum aluminum alloys can significantly extend the service life of these components, reduce maintenance costs, and improve the overall performance of aircraft engines. In addition, tantalum aluminum alloys also have good creep resistance, which enables them to maintain stable shape and size under long-term high-temperature stress conditions.
[0003] Hydrogen is a key impurity in tantalum-aluminum alloys. Hydrogen penetrates the alloy and combines with metal atoms, causing lattice dislocations or cracks, which will lead to a decrease in the toughness of the alloy, an increase in brittleness, and thus a decrease in the mechanical properties of the alloy, commonly known as hydrogen embrittlement. Therefore, it is very important to analyze the hydrogen content in tantalum-aluminum alloys.
[0004] The existing detection method "GBT 15076.15-2008 Chemical Analysis Method of Tantalum and Niobium - Determination of Hydrogen Content" provides a standard method for determining the hydrogen content in tantalum-niobium alloys. It uses the principle of thermal conductivity method, weighs the sample, wraps it with nickel foil, and places it in a high-purity graphite crucible together with tin sheets. The sample is heated. After the sample is heated and melted, the hydrogen in the sample is released. The released hydrogen is loaded into the detection system using a carrier gas. According to the different thermal conductivity of the gas, the hydrogen content in the sample is calculated from the change in the output signal of the thermal conductivity cell. However, for tantalum-aluminum alloys, in actual measurements, impurities and oxides are often attached to the surface of the alloy, which seriously affects the accuracy of the measurement. The alloy sample needs to be pre-treated, and the aluminum is relatively active and easily reacts with the treatment reagent. Especially for low-density samples, the pre-treatment reagent is prone to residue, which seriously affects the measurement results, resulting in the lack of appropriate pre-treatment methods.
[0005] CN116893095A discloses a dissolution method and a detection and analysis method for molybdenum tantalum oxide, wherein molybdenum tantalum oxide powder is mixed with a mixed acid of nitric acid and hydrofluoric acid and heated, and then hydrochloric acid is added, and the mixture is continuously heated and cooled to obtain a clear and transparent solution. The method is to fully dissolve the tantalum alloy to obtain a clear solution for ICP-OES detection and analysis. Existing sample processing methods for tantalum alloys all completely dissolve the alloy and are completely unsuitable for hydrogen content detection.
[0006] Therefore, based on the deficiencies in the prior art, the present invention provides a sample preparation method and a determination method for tantalum-aluminum alloy for hydrogen content detection. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a sample preparation method and a determination method of tantalum-aluminum alloy for hydrogen content detection, to pretreat the tantalum-aluminum alloy sample, to solve the impurity interference in the hydrogen content determination, and to improve the detection accuracy.
[0008] To achieve this object, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a sample of a tantalum-aluminum alloy for hydrogen content detection, the method comprising the following steps:
[0010] (1) Divide the tantalum aluminum alloy to be tested into samples with a size of millimeters;
[0011] (2) placing the sample in a mixed acid solution and performing a first ultrasonic treatment, wherein the mixed acid includes nitric acid and hydrofluoric acid, to complete the pickling process;
[0012] (3) After the pickling process is completed, the sample is placed in water for a second ultrasonic treatment to complete the water washing process;
[0013] (4) After the water washing process is completed, the sample is rinsed with an organic solvent and dried to obtain a tantalum-aluminum alloy sample for testing.
[0014] The sample preparation method provided by the present invention optimizes the pickling pretreatment process for tantalum-aluminum alloys, stably removes impurities and oxides on the surface of tantalum-aluminum alloys, and at the same time avoids the corrosion loss of the relatively active aluminum component. On the other hand, the tantalum-aluminum alloy is first divided and cut, and the alloy to be tested is made into small-sized samples of millimeter level for processing, thereby improving the sample pretreatment effect. At the same time, especially for low-density samples, it avoids residual reagents and impurities inside the sample, thereby improving the accuracy of the sample for hydrogen content determination.
[0015] Preferably, the composition of the tantalum-aluminum alloy to be tested includes: Al 40-60at%, and the balance is Ta.
[0016] Among them, the Al content in the tantalum aluminum alloy to be tested is 40-60at%, for example, it can be 40at%, 45at%, 50at%, 55at% or 60at%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0017] Preferably, the density of the tantalum aluminum alloy to be tested is 80-90%, for example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Preferably, the thickness of the sample is 2-4 mm, for example, 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0019] Preferably, the mass of the sample is 0.06-0.10 g, for example, 0.06 g, 0.07 g, 0.08 g, 0.09 g or 0.10 g, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] Preferably, the volume ratio of nitric acid to hydrofluoric acid is 1:(0.8-1.2), for example, it can be 1:0.8, 1:0.9, 1:1, 1:1.1 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, in the mixed acid solution, the volume ratio of nitric acid, hydrofluoric acid and water is 1:(0.8-1.2):(9-11), for example, it can be 1:1:10, 1:1:9, 1:1:11, 1:0.8:10, 1:1.2:10, 1:0.8:9, 1:0.8:11, 1:1.2:9 or 1:1.2:11, but is not limited to the listed values, and other unlisted values within the numerical range are equally applicable.
[0022] Preferably, the first ultrasound time is 0.5-1.5 min, for example, 0.5 min, 0.8 min, 1 min, 1.2 min or 1.5 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the frequency of the first ultrasound is 30-50 Hz, for example, 30 Hz, 35 Hz, 40 Hz, 45 Hz or 50 Hz, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Preferably, the pickling process further comprises: rinsing with water after the first ultrasound.
[0025] Preferably, the pickling process is performed 2-4 times, for example, 2 times, 3 times or 4 times.
[0026] Preferably, the second ultrasound duration is 0.5-1.5 min, for example, 0.5 min, 0.8 min, 1 min, 1.2 min or 1.5 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0027] Preferably, the frequency of the second ultrasound is 30-50 Hz, for example, 30 Hz, 35 Hz, 40 Hz, 45 Hz or 50 Hz, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0028] Preferably, the water washing process further comprises: rinsing with water after the second ultrasound.
[0029] Preferably, the water washing process is performed 2-4 times, for example, 2 times, 3 times or 4 times.
[0030] Preferably, the organic solvent comprises ethanol.
[0031] Preferably, the drying time is 8-12 min, for example, 8 min, 9 min, 10 min, 11 min or 12 min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] As a preferred technical solution of the sample preparation method provided by the present invention, the sample preparation method comprises the following steps:
[0033] (1) Using a mechanical processing method to split the tantalum aluminum alloy to be tested into a sample with a thickness of 2-4 mm and a mass of 0.06-0.10 g;
[0034] (2) placing the sample in a mixed acid solution and performing a first ultrasound, wherein the mixed acid solution comprises nitric acid, hydrofluoric acid and water, wherein the volume ratio of the nitric acid, hydrofluoric acid and water is 1:(0.8-1.2):(9-11), the frequency of the first ultrasound is 30-50 Hz, the time of the first ultrasound is 0.5-1.5 min, and after the ultrasound is completed, rinsing with deionized water to complete the pickling process, and the pickling process is performed 2-4 times;
[0035] (3) After the pickling process is completed, the sample is placed in water for a second ultrasound, the frequency of the second ultrasound is 30-50 Hz, and the time of the second ultrasound is 0.5-1.5 min. After the ultrasound is completed, the sample is rinsed with deionized water to complete the water washing process. The water washing process is performed 2-4 times;
[0036] (4) After the water washing process is completed, the sample is rinsed with ethanol and then dried for 8-12 minutes to obtain a tantalum-aluminum alloy sample for testing.
[0037] In a second aspect, the present invention provides a method for determining the hydrogen content in a low-density tantalum-aluminum alloy, wherein the method uses a thermal conductivity method to determine the hydrogen content of the tantalum-aluminum alloy sample obtained by the sample preparation method described in the first aspect.
[0038] Preferably, in the hydrogen content determination, the degassing power is 4800-5200 W, for example, 4800 W, 4900 W, 5000 W, 5100 W or 5200 W, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] Preferably, in the hydrogen content determination, the analysis power is 4600-5000W, for example, 4600W, 4700W, 4800W, 4900W or 5000W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] Preferably, in the hydrogen content determination, the carrier gas flow rate is 18-22 psi, for example, 18 psi, 19 psi, 20 psi, 21 psi or 22 psi, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] Preferably, in the hydrogen content determination, the power gas flow rate is 38-42 psi, for example, 38 psi, 39 psi, 40 psi, 41 psi or 42 psi, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The sample preparation method provided by the present invention optimizes the pickling pretreatment of tantalum-aluminum alloy, and cuts the tantalum-aluminum alloy into sizes, thereby improving the treatment effect of the tantalum-aluminum alloy and reducing sample loss. At the same time, it effectively reduces reagent and impurity residues and improves the accuracy of the determination of hydrogen content in the tantalum-aluminum alloy. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0045] In order to clearly illustrate the technical solution of the present invention, in a specific implementation manner, the composition of the tantalum-aluminum alloy to be tested includes: Al 50at%, and the balance is Al. The density of the tantalum-aluminum alloy to be tested is 80%.
[0046] Example 1
[0047] This embodiment provides a sample preparation method of tantalum aluminum alloy for hydrogen content detection, and the sample preparation method comprises the following steps:
[0048] (1) Cut the tantalum aluminum alloy to be tested into a rod-shaped sample with a length of 20 mm, a width of 5 mm, and a thickness of 3 mm, and then cut the rod-shaped sample into specimens with a mass of 0.08 g each along the width direction;
[0049] (2) preparing a mixed acid solution of nitric acid, hydrofluoric acid and water in a volume ratio of 1:1:10, adding the sample and 15 mL of the mixed acid solution into a polytetrafluoroethylene beaker, and performing ultrasonic cleaning in an ultrasonic cleaning machine at a frequency of 40 Hz and a ultrasonic time of 1 min. After the ultrasonic cleaning, the sample was rinsed with deionized water to complete the pickling process. The pickling process was performed 3 times in total;
[0050] (3) After the pickling process is completed, the sample and deionized water are added to a polytetrafluoroethylene beaker and ultrasonicated in an ultrasonic cleaning machine. The ultrasonic frequency is 40 Hz and the ultrasonic time is 1 min. After the ultrasonication, the sample is rinsed with deionized water to complete the water washing process. The water washing process is performed 3 times in total;
[0051] (4) After the water washing process is completed, the sample is rinsed with ethanol and then dried on a heating lamp to remove the ethanol. The drying time is 10 minutes to obtain a tantalum-aluminum alloy sample for hydrogen content detection.
[0052] Example 2
[0053] This embodiment provides a sample preparation method of tantalum aluminum alloy for hydrogen content detection, and the sample preparation method comprises the following steps:
[0054] (1) Cut the tantalum aluminum alloy to be tested into a rod-shaped sample with a length of 20 mm, a width of 5 mm, and a thickness of 2 mm, and then cut the rod-shaped sample into specimens with a mass of 0.06 g each along the width direction;
[0055] (2) preparing a mixed acid solution of nitric acid, hydrofluoric acid and water in a volume ratio of 1:0.8:11, adding the sample and 15 mL of the mixed acid solution into a polytetrafluoroethylene beaker, and performing ultrasonic cleaning in an ultrasonic cleaning machine at a frequency of 40 Hz and a ultrasonic time of 0.5 min. After the ultrasonic cleaning, the sample was rinsed with deionized water to complete the pickling process. The pickling process was performed 4 times in total;
[0056] (3) After the pickling process is completed, the sample and deionized water are added to a polytetrafluoroethylene beaker and ultrasonicated in an ultrasonic cleaning machine. The ultrasonic frequency is 40 Hz and the ultrasonic time is 0.5 min. After the ultrasonication is completed, the sample is rinsed with deionized water to complete the water washing process. The water washing process is performed 4 times in total;
[0057] (4) After the water washing process is completed, the sample is rinsed with ethanol and then dried on a heating lamp to remove the ethanol. The drying time is 8 minutes, thereby obtaining a tantalum-aluminum alloy sample for hydrogen content detection.
[0058] Example 3
[0059] This embodiment provides a sample preparation method of tantalum aluminum alloy for hydrogen content detection, and the sample preparation method comprises the following steps:
[0060] (1) Cut the tantalum aluminum alloy to be tested into a rod-shaped sample with a length of 20 mm, a width of 5 mm, and a thickness of 4 mm, and then cut the rod-shaped sample into specimens with a mass of 0.10 g each along the width direction;
[0061] (2) preparing a mixed acid solution of nitric acid, hydrofluoric acid and water in a volume ratio of 1:1.2:9, adding the sample and 15 mL of the mixed acid solution into a polytetrafluoroethylene beaker, and performing ultrasonic cleaning in an ultrasonic cleaning machine at a frequency of 40 Hz and a ultrasonic time of 1.5 min. After the ultrasonic cleaning, the sample was rinsed with deionized water to complete the pickling process. The pickling process was performed twice in total;
[0062] (3) After the pickling process is completed, the sample and deionized water are added to a polytetrafluoroethylene beaker and ultrasonicated in an ultrasonic cleaning machine. The ultrasonic frequency is 40 Hz and the ultrasonic time is 1.5 min. After the ultrasonication is completed, the sample is rinsed with deionized water to complete the water washing process. The water washing process is performed twice in total;
[0063] (4) After the water washing process is completed, the sample is rinsed with ethanol and then dried on a heating lamp to remove the ethanol. The drying time is 12 minutes to obtain a tantalum-aluminum alloy sample for hydrogen content detection.
[0064] Example 4
[0065] This embodiment provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the volume ratio of nitric acid, hydrofluoric acid and water is controlled to be 1:0.5:10, and the rest is the same as Example 1.
[0066] Example 5
[0067] This embodiment provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the volume ratio of nitric acid, hydrofluoric acid and water is controlled to be 1:1.5:10, and the rest is the same as Example 1.
[0068] Example 6
[0069] This embodiment provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the volume ratio of nitric acid, hydrofluoric acid and water is controlled to be 1:1:5, and the rest is the same as Example 1.
[0070] Example 7
[0071] This embodiment provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the volume ratio of nitric acid, hydrofluoric acid and water is controlled to be 1:1:15, and the rest is the same as Example 1.
[0072] Comparative Example 1
[0073] This comparative example provides a method for preparing a sample of a tantalum-aluminum alloy for hydrogen content detection. Compared with Example 1, the tantalum-aluminum alloy to be tested is not cut and trimmed in step (1). The size of the tantalum-aluminum alloy to be tested is 25 mm in length, 10 mm in width and thickness, and the rest is the same as Example 1.
[0074] Comparative Example 2
[0075] This comparative example provides a method for preparing a sample of tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the pickling process described in step (2) is not performed, and the rest is the same as Example 1.
[0076] Comparative Example 3
[0077] This comparative example provides a method for preparing a sample of tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the water washing process described in step (3) is not performed, and the rest is the same as Example 1.
[0078] Comparative Example 4
[0079] This comparative example provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the pickling process in step (2) uses a nitric acid solution. In the nitric acid solution, the volume ratio of nitric acid to water is 2:10, that is, an equal volume of hydrofluoric acid is replaced by nitric acid. The rest is the same as Example 1.
[0080] Comparative Example 5
[0081] This comparative example provides a sample preparation method for tantalum aluminum alloy for hydrogen content detection. Compared with Example 1, the pickling process in step (2) uses a hydrofluoric acid solution. In the hydrofluoric acid solution, the volume ratio of hydrofluoric acid to water is 2:10, that is, an equal volume of nitric acid is replaced by hydrofluoric acid. The rest is the same as Example 1.
[0082] The loss rates of the tantalum-aluminum alloys before and after sample preparation provided in the embodiments and comparative examples were measured and calculated, and 0.15 g of the obtained tantalum-aluminum alloy samples were respectively taken for detection in a hydrogen analyzer (Leco RHEN602). The measurement parameters included: degassing power of 5000 W, analysis power of 4800 W, carrier gas flow rate of 20 psi, and power gas flow rate of 40 psi. The results are listed in Table 1.
[0083] Table 1
[0084]
[0085]
[0086] As can be seen from Table 1, the sample preparation method provided by the present invention can effectively treat tantalum-aluminum alloy, remove surface impurities and oxides, avoid alloy corrosion, improve the accuracy of hydrogen content test of tantalum-aluminum alloy, and control the relative standard deviation of the test to below 8.5%. Compared with Example 1, in Examples 4-7, after adjusting the volume ratio of the acid solution, the accuracy of the sample test decreased.
[0087] Compared with Example 1, in Comparative Example 1, the sample is not segmented, the treatment effect on the sample with low density is reduced, and the measurement accuracy is reduced; in Comparative Example 2, no acid washing is performed, and only one acid is used for treatment in Comparative Examples 4-5, the sample impurities cannot be effectively removed, and the measurement accuracy is significantly reduced; in Comparative Example 3, no water washing is performed, which easily causes the acid to remain in the pores of the sample, reducing the measurement accuracy.
[0088] In summary, the sample preparation method provided by the present invention optimizes the pickling pretreatment of tantalum-aluminum alloy, and cuts the tantalum-aluminum alloy into sizes, thereby improving the treatment effect of the tantalum-aluminum alloy and reducing sample loss. At the same time, it effectively reduces reagent and impurity residues and improves the accuracy of the hydrogen content determination of the tantalum-aluminum alloy.
[0089] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sample of tantalum-aluminum alloy for hydrogen content detection, characterized in that: The sample preparation method comprises the following steps: (1) Divide the tantalum aluminum alloy to be tested into samples with a size of millimeters; (2) placing the sample in a mixed acid solution and performing a first ultrasonic treatment, wherein the mixed acid includes nitric acid and hydrofluoric acid, to complete the pickling process; (3) After the pickling process is completed, the sample is placed in water for a second ultrasonic treatment to complete the water washing process; (4) After the water washing process is completed, the sample is rinsed with an organic solvent and dried to obtain a tantalum-aluminum alloy sample for testing.
2. The sample preparation method according to claim 1, characterized in that: The composition of the tantalum-aluminum alloy to be tested includes: Al 40-60at%, and the balance is Ta; Preferably, the density of the tantalum-aluminum alloy to be tested is 80-90%.
3. The sample preparation method according to claim 1 or 2, characterized in that: The thickness of the sample is 2-4 mm; Preferably, the mass of the sample is 0.06-0.10 g.
4. The sample preparation method according to any one of claims 1 to 3, characterized in that: The volume ratio of the nitric acid to the hydrofluoric acid is 1:(0.8-1.2); Preferably, in the mixed acid solution, the volume ratio of nitric acid, hydrofluoric acid and water is 1:(0.8-1.2):(9-11).
5. The sample preparation method according to any one of claims 1 to 4, characterized in that: The first ultrasound duration is 0.5-1.5 min; Preferably, the frequency of the first ultrasound is 30-50 Hz; Preferably, the pickling process further comprises: rinsing with water after the first ultrasound; Preferably, the pickling process is performed 2-4 times.
6. The sample preparation method according to any one of claims 1 to 5, characterized in that: The second ultrasound duration is 0.5-1.5 min; Preferably, the frequency of the second ultrasound is 30-50 Hz; Preferably, the water washing process further comprises: rinsing with water after the second ultrasound; Preferably, the water washing process is performed 2-4 times.
7. The sample preparation method according to any one of claims 1 to 6, characterized in that: The organic solvent includes ethanol; Preferably, the drying time is 8-12 minutes.
8. The sample preparation method according to any one of claims 1 to 7, characterized in that: The sample preparation method comprises the following steps: (1) Using a mechanical processing method to split the tantalum aluminum alloy to be tested into samples with a thickness of 2-4 mm and a mass of 0.06-0.10 g; (2) placing the sample in a mixed acid solution and performing a first ultrasound, wherein the mixed acid solution comprises nitric acid, hydrofluoric acid and water, wherein the volume ratio of the nitric acid, hydrofluoric acid and water is 1:(0.8-1.2):(9-11), the frequency of the first ultrasound is 30-50 Hz, the time of the first ultrasound is 0.5-1.5 min, and after the ultrasound is completed, rinsing with deionized water to complete the pickling process, and the pickling process is performed 2-4 times; (3) After the pickling process is completed, the sample is placed in water for a second ultrasound, the frequency of the second ultrasound is 30-50 Hz, and the time of the second ultrasound is 0.5-1.5 min. After the ultrasound is completed, the sample is rinsed with deionized water to complete the water washing process. The water washing process is performed 2-4 times; (4) After the water washing process is completed, the sample is rinsed with ethanol and then dried for 8-12 minutes to obtain a tantalum-aluminum alloy sample for testing.
9. A method for determining the hydrogen content in tantalum aluminum alloy, characterized in that: The determination method uses a thermal conductivity method to determine the hydrogen content of the tantalum-aluminum alloy sample obtained by the sample preparation method according to any one of claims 1 to 8.
10. The measuring method according to claim 9, characterized in that In the hydrogen content determination, the degassing power is 4800-5200W; Preferably, in the hydrogen content determination, the analysis power is 4600-5000W; Preferably, in the hydrogen content determination, the carrier gas flow rate is 18-22 psi; Preferably, in the hydrogen content determination, the power gas flow rate is 38-42 psi.
Citation Information
Patent Citations
Method for determining oxygen / nitrogen / hydrogen content in interalloy for titanium alloys
CN104764695A
Tantalum sample pretreatment method for glow discharge mass spectrometry detection and detection method
CN118533597A
Sample preparation method and detection method for detecting carbon content in aluminum sample by glow discharge mass spectrometry
CN118706565A
Iron-cobalt-tantalum alloy powder preparation method, iron-cobalt-tantalum alloy powder and use thereof
WO2022041741A1
Cited By
Detection method for detecting hydrogen content in aluminum-chromium alloy
CN120820581A